Electroacupuncture Pretreatment at Zusanli (ST36) Ameliorates Hepatic Ischemia/Reperfusion Injury in Mice by Reducing Oxidative Stress via Activating Vagus Nerve-Dependent Nrf2 Pathway - Jiang H; Shang Z; You L; Zhang J; Jiao J; Qian Y; Lin J; Wang F; Gao Y; Kong X; Sun X (Dove Medical Press, 2023)
Haochen Jiang,1,2,* Zhi Shang,2,* Liping You,1,2,* Jinghao Zhang,1 Junzhe Jiao,2 Yihan Qian,2 Jiacheng Lin,2 Fang Wang,2 Yueqiu Gao,1 Xiaoni Kong,2 Xuehua Sun1 1Department of Liver Diseases, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 2Central Laboratory, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Xuehua Sun, Department of Liver Diseases, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China, Email susan_sxh@shutcm.edu.cn Xiaoni Kong, Central Laboratory, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China, Email xiaonikong@shutcm.edu.cnBackground and Purpose: Current pharmacological approaches to prevent hepatic ischemia/reperfusion injury (IRI) are limited. To mitigate hepatic injury, more research is needed to improve the understanding of hepatic IRI. Depending on traditional Chinese medicine (TCM) theory, acupuncture therapy has been used for the treatment of ischemic diseases with good efficacy. However, the efficacy and mechanism of acupuncture for hepatic IRI are still unclear.Methods: Blood provided to the left and middle lobe of mice livers was blocked with a non-invasive clamp and then the clamps were removed for reperfusion to establish a liver IRI model. Quantitative proteomics approach was used to evaluate the impact of EA pretreatment on liver tissue proteome in the IRI group. Serum biochemistry was used to detect liver injury, inflammation, and oxidative stress levels. H&E staining and TUNEL staining were used to detect hepatocyte injury and apoptosis. Immunohistochemistry and ELISA were used to detect the degree of inflammatory cell infiltration and the level of inflammation. The anti-inflammatory and antioxidant capacities were detected by Quantitative RT-PCR and Western blotting.Results: We found that EA at Zusanli (ST36) has a protective effect on hepatic IRI in mice by alleviating oxidative stress, hepatocyte death, and inflammation response. Nuclear factor E2-related factor 2 (Nrf2) as a crucial target was regulated by EA and was then successfully validated. The Nrf2 inhibitor ML385 and cervical vagotomy eliminated the protective effect in the EA treatment group.Conclusion: This study firstly demonstrated that EA pretreatment at ST36 significantly ameliorates hepatic IRI in mice by inhibiting oxidative stress via activating the Nrf2 signal pathway, which was vagus nerve-dependent.Keywords: inflammation, liver, proteomics